2019
DOI: 10.3390/j2030019
|View full text |Cite
|
Sign up to set email alerts
|

The Confidence of Undergraduate Dental Students When Undertaking Indirect Restorations

Abstract: The General Dental Council expects United Kingdom graduating dentists to be competent at providing crown and bridge treatments and graduating students should feel confident to undertake these treatments. The aim of this study was to explore the confidence of undergraduate dental students when providing crown and fixed dental prosthesis treatments. An anonymous questionnaire was distributed to all (n = 198) undergraduate students in Years 3 to 5 at Bristol Dental School. The questionnaire comprised confidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Correspondingly, the consistent use of FGC balanced its established clinical longevity 8 with its lack of aesthetics, the rising cost of gold and a move away from traditional laboratory techniques to digital processes. It has previously been demonstrated that undergraduate students in more senior years had good levels of confidence in performing these types of crown preparations after receiving formal didactic and practical teaching 9 …”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, the consistent use of FGC balanced its established clinical longevity 8 with its lack of aesthetics, the rising cost of gold and a move away from traditional laboratory techniques to digital processes. It has previously been demonstrated that undergraduate students in more senior years had good levels of confidence in performing these types of crown preparations after receiving formal didactic and practical teaching 9 …”
Section: Discussionmentioning
confidence: 99%